A pathway for promoting bioelectrochemical performance of microbial fuel cell by synthesizing graphite carbon nitride doped on single atom catalyst copper as cathode catalyst. (March 2023) - Chen, Junfeng; Yang, Jiaqi; Tian, Jiarui; Zhang, Yiwen; Wu, Yiqun; Zhao, Kunqi; Wang, Renjun; Yang, Yuewei; Liu, Yanyan
Graphical abstract: Highlights: The composite Cu-SA/CN was prepared by a simple distributed feeding method. Cu-SA/CN possessed good structure and electrochemical activity. The maximum power density of Cu-SA/CN3-MFC was 456.976 mW/m 2 . Cu-SA/CN3 improved the conductivity, stability and high oxygen reduction activity. Abstract: In this study, a simple distributed feeding method was used to dope graphite phase carbon nitride (g-C3 N4 ) on single atom catalyst (SAC) copper (Cu) to form composite material (Cu-SA/CN). Cu-SA/CN was formed by mutual doping of polyhedral block Cu and irregular g-C3 N4 . There were obvious crystal face peaks at 28.4, 43.3, 47.3 and 56.2°. Large solid Cu and small irregular g-C3 N4 were successfully combined and C, Cu, N and O elements were uniformly distributed on the surface of Cu-SA/CN. The valence bond of N -CN, C-NC, CC and OH was found. When the Cu content was 0.03 mol, Cu-SA/CN3 showed excellent redox activity. The maximum power density of Cu-SA/CN3-MFC was 456.976 mW/m 2, the maximum voltage was 599 mV, which could be stable for 7 d. Cu-SA/CN3 was proved to provide more electrically active sites, strong catalytic oxygen reduction ability and conductivity.